Effect of realistic simulation combined to theory on self-confidence and satisfaction of nursing professionals - Hanna Clara Teixeira Mesquita; Breno de Sousa Santana; Marcia Cristina da Silva Magro (Universidade Federal do Rio de Janeiro, 2019)
Abstract Objective: To compare the effect of the use of the simulation strategy combined to theory with the simulation, per se, on the gain of self-confidence in nursing professionals during the management of the patient in cardiopulmonary arrest. Method: Quasi-experimental study with pre and post-tests, quantitative approach. Convenience sample composed of 53 professionals, divided into a control and experimental groups. The strategy was the intervention. A structured questionnaire and the satisfaction and self-confidence scale were used for data collection. Results with p≤0.05 were considered significant. Results: Professionals were predominantly young (33.2 ± 6.5 years) and females (84.9%). In the experimental group there was no significant difference (p=0.1 vs p=0.4), but self-confidence increased significantly among the professionals in the experimental group in relation to the control (p=0.007 vs p=0.06). Conclusion: The level of self-confidence of the nursing professionals for patient care in cardiopulmonary arrest improved significantly after using the combined simulation theory.